Experience of laparoscopic cholecystectomy under spinal anesthesia with low-pressure pneumoperitoneum - prospective study of 300 cases - Manoranjan Kar (The Saudi Journal of Gastroenterology, 2011)
Introduction : Having long experience of open upper abdominal surgery under spinal anesthesia and laparoscopic cholecystectomy under general anesthesia, we performed this study of laparoscopic cholecystectomy with low-pressure pneumoperitoneum under spinal anesthesia to assess its safety and feasibility. Materials and Methods : In a private rural health set-up, 300 patients were selected prospectively for laparoscopic cholecystectomy under low-pressure (8 mm) pneumoperitoneum under spinal anesthesia in a span of three years. Only 3.5 ml of 0.5% bupivacaine was used for spinal anesthesia. Fourth port positioned at lower than usual at the level of umbilicus, change of position of the table with different stages of operation, massaging of right shoulder in cases of shoulder pain, removal of smoke if formed during dissection to diminish shoulder pain and holding the body of the gallbladder by the fourth port grasper at the level of lower margin of the liver in cases of long gallbladder were some modifications of standard laparoscopic cholecystectomy made in this study. Results: We successfully performed the operations in 291 patients without major complications. Four patients denied operation under spinal anesthesia. Spinal anesthesia was converted to general anesthesia in two patients due to severe shoulder pain. The operation was converted to open cholecystectomy in three patients. Mean age was 34.6 years (range 21-82 years). Mean BMI was -23.1 (range 20.8-28.3). Mean duration of operation was 39.6 min (range 18-78 min). Mean O 2 saturation was 97.6%. Mean peak respiratory rate was 23.4 (range 16-38). 90.08% patients complained of right shoulder pain - most of them managed by shoulder massage alone. All patients were satisfied on follow up. Conclusion : Laparoscopic cholecystectomy under spinal anesthesia with low-pressure pneumoperitoneum can be performed safely and satisfactorily without major complications by experienced surgeons.